Highly Efficient Visible‐Light‐Driven Photocatalytic Hydrogen Production Using Robust Noble‐Metal‐Free Zn0.5Cd0.5S@Graphene Composites Decorated with MoS2 Nanosheets. Issue 12 (10th May 2020) - Madhusudan, Puttaswamy; Shi, Run; Chandrashekar, Bananakere Nanjegowda; Xiang, Shengling; Smitha, Ankanahalli Shankaregowda; Wang, Weijun; Zhang, Haichao; Zhang, Xian; Amini, Abbas; Cheng, Chun
Abstract: Solar water splitting using semiconductor photocatalysts is considered to be one of the economical and significant techniques for hydrogen evolution. In this study, graphene–Zn x Cd1− x S (ZCS) heterojunction is fabricated by hydrothermal method followed by simple photodeposition of ultrathin few layers of molybdenum sulfide (MoS2 ) nanosheets. The results show that compared with pristine ZCS and 1 wt% graphene mixed ZCS photocatalysts, the 1 wt% graphene and 1 wt% MoS2 photodeposited ZCS composited sample shows 39.5 mmol h −1 g −1 hydrogen production activity, which is 6.9 and 1.9 times significantly higher, respectively, with an apparent quantum yield of 53% at 420 nm visible light is recorded. The improved photocatalytic activity can be attributed to the formation of heterostructure interface between p‐type MoS2 nanosheets with n‐type ZCS host, which allows for the faster transfer of the photogenerated electrons and thus significantly promotes the separation of photogenerated charge carriers. Abstract : Graphene zinc cadmium sulphide (ZCS) heterojunction is fabricated followed by photodeposition of MoS2 nanosheet. The interface between the graphene and MoS2 with ZCS effectively suppresses the charge recombination. Consequently, the sample shows outstanding hydrogen production activity of 39.5 mmol h −1 g −1, which is higher than ZCS and graphene composited ZCS. Furthermore, the mechanism for enhanced photoactivity is also demonstrated.